Mapping agricultural responses to water supply shocks in large irrigation systems, southern India - Biggs, Trent W.; Gangadhara Rao, Parthasaradhi; Bharati, Luna (Elsevier, 2010)
Irrigated agriculture experienced a water supply shock during a drought in southern India in 2002-2003. In this paper, hotspots of agricultural change were mapped and put in the context of hydrology and water management. Time series of MODIS imagery taken every eight days before (2001-2002) and during (2002-2003) the supply shock were combined with agricultural census data to document changes in cropping patterns in four large irrigation projects in the downstream sections of the Krishna and Godavari River basins (total command area 18,287km2). The area cropped in rice in the four irrigated command areas decreased by 32% during the drought year, and rice production in the two districts that experienced the largest flow reductions fell below production levels of 1980. The irrigation project that showed the largest change in double cropped area (-90%) was upstream of the Krishna Delta. In the Krishna Delta, large areas changed from rice-rice to rice-gram double cropping. Historical water management contributed to the vulnerability of rice production to drought: the main reservoir in the system was drained to dead storage levels by the end of each growing season over 1968-2000, with little carryover storage. The land cover change maps suggested that the lower Krishna Basin has experienced a "hard landing? during basin closure, and revised management strategies that account for the new flow regime will be required to maintain agricultural production during droughts.